Perlindungan Konsumen dari Ancaman Produk Kedaluwarsa: Perspektif Hukum dan Etika - Wahid Bagus Sanjaya; Romi Faslah (CV. ITTC INDONESIA, 2025)
Consumers are among the most vulnerable groups in trade because they often lack sufficient information about the products they consume, particularly regarding expiration dates. Consuming expired goods, especially food, beverages, and medicines, can result in serious health issues, psychological distress, and economic losses. This article aims to analyze the legal protections available to consumers in Indonesia regarding expired goods, including civil, administrative, and criminal liabilities imposed on business actors. In addition, the paper reviews Islamic law and customary law perspectives, both of which emphasize the importance of justice, transparency, and honesty in trade. The normative juridical approach is used to examine relevant legislation and literature. The findings suggest that while regulatory frameworks exist, enforcement and public awareness remain insufficient. Therefore, collaborative efforts among government agencies, businesses, and consumers are essential to ensuring consumer rights and public welfare.